Association between personality disorders and migraine. A narrative review - Ewa Olek; Oliwia Szewczyk; Karolina Czarnecka; Anna Korczak; Katarzyna Burda; Emilia Wójcik; Olga Łopacińska; Katarzyna Stańczyk; Aleksandra Korn; Justyna Jędrzejczyk (Kazimierz Wielki University, 2024)
Introduction: Migraine is one of the most prevalent types of headache and is a subject of many clinical trials. There are various risk factors associated with migraine occurrence, from hormonal and genetic to environmental. It is observed that some migraineurs have specific psychological features- sometimes called as migraine personality. This encouraged researchers to evaluate migraine patients in terms of psychiatric co-existing conditions. Aim of study: The main aim of the study was to examine the relationship between migraine and psychiatric comorbidities, primarily personality disorders. Materials and methods: This article is based on the literature found in PubMed and Google Scholar Database with the use of keywords such as "migraine", "headache factors", "personality disorder", "migraine personality", "migraine education", "borderline personality disorder", "anxious personality disorder", "migraine health", "depression and migraine", "medication over-use in migraine", "migraine comorbidities", "depression", "anxiety". Results: Investigation of available literature revealed the connection between migraine and personality disorders. Psychiatric comorbidities worsen the treatment prognosis, are a risk factor of medication overuse and chronic headaches. Conclusion: Psychiatric comorbidities are frequent among migraineurs. Clinical evaluation of these patients should be complex and contain psychological and psychiatric analysis, especially in patients resistant to standard treatment.